Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematika Materi Pola Bilangan Menggunakan Model Problem Based Learning pada Siswa Kelas IV SDN Pasir Indah Ciater - Fina Lapiyah; Dayat Dayat; Badru Sohim (Jurnal Pendidikan Educandum, 2026)
Problem solving ability is an essential skill in mathematics learning as it trains students to think critically, logically, and systematically. However, observations at SDN Pasir Indah Ciater showed that most fourth-grade students still had difficulty understanding problems, planning strategies, and checking solutions. This study aims to describe teachers’ efforts to improve students’ mathematical problem-solving skills through the Problem Based Learning (PBL) model on number pattern material, as well as analyze supporting and inhibiting factors and its relevance to modern learning. This research used a qualitative descriptive method involving a teacher and sixteen fourth-grade students of SDN Pasir Indah Ciater. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The results show that the implementation of the PBL model improved students’ mathematical problem-solving skills. Students became more active, enthusiastic, and critical in finding solutions, while teachers acted as facilitators. Supporting factors included concrete media and student collaboration, while obstacles were limited time and varied initial abilities. Overall, PBL is relevant to 21st-century learning because it fosters critical, collaborative, and communicative skills.